When East meets West: gaze-contingent Blindspots abolish cultural diversity in eye movements for faces - Sébastien Miellet; Lingnan He; Xinyue Zhou; Junpeng Lao; Roberto Caldara (Bern Open Publishing, 2012)
Culture impacts on how people sample visual information for face processing. Westerners deploy fixations towards the eyes and the mouth to achieve face recognition. In contrast, Easterners reach equal performance by deploying more central fixations, suggesting an effective extrafoveal information use. However, this hypothesis has not been yet directly investigated, i.e. by providing only extrafoveal information to both groups of observers. We used a parametric gaze-contingent technique dynamically masking central vision - the Blindspot - with Western and Eastern observers during face recognition. Westerners shifted progressively towards the typical Eastern central fixation pattern with larger Blindspots, whereas Easterners were insensitive to the Blindspots. These observations clearly show that Easterners preferentially sample information extrafoveally for faces. Conversely, the Western data also show that culturally-dependent visuo-motor strategies can flexibly adjust to constrained visual situations.